PENGARUH PEMBERIAN AROMA TERAPI LAVENDER PADA IBU NIFAS DENGAN NYERI JAHITAN PERINEUM DI PUSKESMAS 7 UlU - Harianja, Winda yunyaty; Wulandhary, Anggraini wulan (Jurnal Ilmu Kebidanan, 2026)
Background : Postpartum mothers almost always experience various discomforts caused by uterine involution, perineal trauma or tears, whether spontaneous or due to an episiotomy, breast engorgement, labor fatigue, and other physiological changes. The most common discomforts include abdominal pain (afterpains), vaginal and perineal pain, breast swelling and tenderness, excessive sweating, constipation, hemorrhoids, and more. Pain is an unpleasant subetive and emotional sensory experience that is obtained related to real tissue damage, potentially damaged or describing the condition of the occurrence of damage. Treatment that is often used to reduce pain in the form of pharmacological treatment and non-pharmacological therapy, one of which is relaxation of distraction, warm compress, and aromatherapy. The mechanism of aromatherapy in the human body takes place through two physiological systems, namely the circulation of the body and the olfactory system, fragrance can affect a person's prikis, memory, and emotions. One of the aromatherapy that can be used is lavender aromatherapy. Lavender aromatherapy can provide calmness, comfort, confidence, reduce stress, reduce pain, unbalanced emotions, panic, lavender can reduce pain and can provide relaxation. Method : Bivariate analysis test in this study using Wilcoxon analysis. The place to take research is in 7 Ulu Health Center. Sampling with non-probability sampling techniques of purposive sampling type. Samples taken as many as 30 mothers nifas 6 hours post partum. The main instrument used in this study is the assessment format. Results : Mann Whitney test results obtained 0.000 < 0.05, which means there is an influence of lavender therapy aroma giving in Nifas mother with perineum stitch pain in 7 Ulu health center Conclusion: There is an influence of lavender aroma in the mother nifas with perineum pain